The Applied Legitimacy Index: A New Approach to Measuring Judicial Legitimacy. (2nd May 2019) - Badas, Alex
Abstract : Objectives: This article advances criticisms of the traditional legitimacy index as it relates to determining whether ideological distance predicts an individual's willing to sanction the Court. As a solution to these criticisms, this article develops a new measure of judicial legitimacy, the applied legitimacy index. Methods: Using data from the American Panel Survey and item response theory models, this article estimates the applied legitimacy index. Ordinary least squares regression models then compare the effect ideological distance has on both the traditional legitimacy index and the newly developed applied legitimacy index. Results: The results indicate that those who are ideologically distant from the Court have diminished views of the Court's applied legitimacy. The substantive effect of ideological distance is much larger for applied legitimacy than when compared with traditional legitimacy. Conclusions: This article suggests that the traditional legitimacy index may overestimate loyalty to the Court and underestimate the extent to which individuals are willing to sanction an ideologically distant Court. Based on this, the article advocates that scholars adopt the applied legitimacy index in future studies.